Adaptive algorithm based on time window partitioning for discrete and dynamic berth-scheduling problem - Golias, Mihalis; Boile, Maria; Theofanis, Sotiris (My University, 2009)
The berth-scheduling problem is considered with the objective of increasing customer satisfaction by minimizing the late berthing or departure and maximizing the early and timely berthing or departure of vessels. Vessel priority also is considered through the use of weights. An adaptive local search heuristic is developed to solve the resulting problem using a Markovian walk and a time window partitioning approach to improve convergence patterns and the objective function values. Results obtained from the heuristic are shown to be robust, and convergence rates and patterns are promising.